Dissemination and Cultural Change as an Alternative Business Value Proposition in the Construction Industry: Manni Group Case Study. (November 2021) - Tinazzi, Umberto
There is a gap of knowledge between practitioners about the off-site construction. For this reason, the Manni Group case study presented in this article highlights the positive role of dissemination as business value proposition support in the context of off-site construction industry. The Manni Group involved opinion leaders, professionals, universities and industrial partners in a network of dissemination that, going beyond the concept of advertising, it generated a multiple effect of value creation between the direct and indirect involved stakeholders. Dissemination emerges as a model of action that creates impacts on cultural change. It is scalable and applicable in many areas where actors have the right competences to manage the dissemination. Wherever there is a knowledge gap or friction towards new techniques and methodologies, the model is able to create value for companies and stakeholders involved in the emerging network.